PERAN PEMERINTAH KABUPATEN KENDAL DALAM MENYELENGGARAKAN PENDIDIKAN NON FORMAL SEBAGAI UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI KABUPATEN KENDAL - Dinisti, Afsih Lisani (Journal of Politic and Government Studies, 2017)
PERAN PEMERINTAH KABUPATEN KENDAL DALAM MENYELENGGARAKAN PENDIDIKAN NON FORMAL SEBAGAI UPAYA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DI KABUPATEN KENDALAFSIH LISANI DINISTI(DEPARTEMEN POLITIK DAN PEMERINTAHAN FISIP UNDIP)Abstract: The Role Of Kendal Regency Government In Organizing Non Formal Education As An Effort To Improve Quality Of Human Resources In Kendal Regency.Kendal Regency is one of the areas in Central Java province with high poverty levels. The high levels of poverty in Kendal caused by the quality of Human Resources is low. While the low quality of Human Resources in Kendal is influenced by education level of society. The education level of the community in Kendal regency is dominated by people with a category not/do not complete primary school. From that problem is need for follow-up in the fulfillment of public education throughout life. One of the efforts undertaken by the Government of Kendal is the issuance of District Regulation Kendal No. 10 of 2012 on the Management and Delivery of Education, where education in Kendal not only be done through formal education (schools), but also through non-formal education. This research focuses on the role of Kendal Regency Government in organizing non formal education as an effort to improve quality of human resources in Kendal Regency.The type of research is qualitative descriptive. Data obtained from the primary and secondary data, using purposive sampling techniques for the selecting informants. Data collection techniques used were in-depth interviews and documents study.The results showed that the role of the Government of Kendal in organizing non-formal education as an effort to improve the quality of human resources in Kendal are the organizers, meaning that the Government of Kendal is a party to arouse, encourage, facilitate, and manage ideas and activities development in the community in the field of non-formal education. Implementation of these roles are divided into three phases: preparation, implementation, and evaluation. However there are several factors that constraint, the first is financial and the second is is the human resource in this regard is the non formal education teachers.The writer given to the Kendal Regency Government and the people who follow non-formal education in Kendal. For Kendal Regency Government should provide more support on non formal education of organizing in order to become a partner level with formal education. As for the people who follow non-formal education in Kendal should be able to utilize the facilities provided by the Government of Kendal wisely, because such facilities as an opportunity to improve the quality of society.Keywords: Role of Government, Non-Formal Education, Human Resources